2011
DOI: 10.1016/j.chembiol.2011.07.010
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Disruption of the CCR5 Gene in Human Hematopoietic Stem Cells Stimulated by Peptide Nucleic Acids

Abstract: SUMMARY Peptide nucleic acids (PNAs) bind duplex DNA in a sequence-specific manner, creating triplex structures that can provoke DNA repair and produce genome modification. CCR5 encodes a chemokine receptor required for HIV-1 entry into human cells and individuals carrying mutations in this gene are resistant to HIV-1 infection. Transfection of human cells with PNAs targeted to the CCR5 gene, plus donor DNAs designed to introduce stop codons mimicking the naturally occurring CCR5-delta32 mutation, produced 2.4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
66
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(68 citation statements)
references
References 34 publications
1
66
0
1
Order By: Relevance
“…Moreover, transplantation of CCR5 homozygous mutant HSPCs provides long-term protection against HIV rebound even after discontinuation of antiretroviral therapy (Allers et al, 2011; Hutter et al, 2009). Several attempts have been made to target CCR5 in T cells (Perez et al, 2008; Tebas et al, 2014) and HSPCs (Holt et al, 2010; Schleifman et al, 2011) though the efficiency of gene targeting was not sufficient to protect against viral recrudescence (Tebas et al, 2014). Recently, CCR5 has been targeted using CRISPR/Cas9 in cell lines (Cho et al, 2013) and iPS cells (Ye et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, transplantation of CCR5 homozygous mutant HSPCs provides long-term protection against HIV rebound even after discontinuation of antiretroviral therapy (Allers et al, 2011; Hutter et al, 2009). Several attempts have been made to target CCR5 in T cells (Perez et al, 2008; Tebas et al, 2014) and HSPCs (Holt et al, 2010; Schleifman et al, 2011) though the efficiency of gene targeting was not sufficient to protect against viral recrudescence (Tebas et al, 2014). Recently, CCR5 has been targeted using CRISPR/Cas9 in cell lines (Cho et al, 2013) and iPS cells (Ye et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7][8] In addition, these compounds have been used to inhibit transcription and to stimulate site-directed recombination of a co-transfected donor DNA, resulting in correction of a mutation in the target gene. [9][10][11][12] TFOs have also been used to study mechanisms of DNA damage and repair, recombination and structurally induced genomic instability. Previous studies have demonstrated that triplex formation itself induces mutagenesis and stimulates DNA repair.…”
Section: Introductionmentioning
confidence: 99%
“…However, HSCs do not express CCR5, and it is therefore not possible to selectively enrich for this population prior to differentiation. Nonetheless, numerous preclinical studies have shown high levels of disruption and engraftment of CCR5 gene-modified cells, which retained the ability to differentiate into numerous lineages and resist viral infection [73,74,84]. While stem cells provide a long-lived source of genetically modified cells that can differentiate into various lineages, they may not be the right choice for engineering resistance until it can be confirmed that disruption does not affect the function of all derived cell types.…”
Section: Considerations For Future Developmentmentioning
confidence: 97%